The Impact of Lifestyle, Social Media Marketing, and Influencer Marketing on Purchase Decision for Ayam Geprek Culinary Business - Barusman, Andala Rama Putra; Suwandi, Felicia (International Journal of Psychosocial Rehabilitation, 2020)
The modern lifestyle of people is very close with social media, creating a social media dependent community to fulfil their needs. The purpose of this study is to determine the impact of lifestyle, social media marketing and influencer marketing on purchase decision of Ayam Geprek Culinary Business specifically in Bandar Lampung. The sample was taken using purposive random sampling method. Total samples were taken from 1000 ayam geprek customers who have tasted food in 5 culinary businesses. Data analysis tool used is multiple regression analysis with SPSS 23.0.The results of the study have shown that the lifestyle, social media marketing, influencer marketing variable significantly influence purchase decision and as simultaneously influence purchase decision of ayam geprek business culinary in Bandar Lampung.